Proteome and Acetyl-Proteome Profiling of Camellia sinensis cv. ‘Anji Baicha’ during Periodic Albinism Reveals Alterations in Photosynthetic and Secondary Metabolite Biosynthetic Pathways - Xu, Yan-Xia; Chen, Wei; Ma, Chun-Lei; Shen, Si-Yan; Zhou, Yan-Yan; Zhou, Lian-Qi; Chen, Liang (Frontiers in Plant Science, 2017)
Tea leaf color is not only important from an aesthetics standpoint but is also related to tea quality. To investigate the molecular mechanisms that determine tea leaf color, we examined Camellia sinensis cv. ‘Anji Baicha’ (an albino tea cultivar) by tandem mass tag isobaric labeling to generate a high-resolution proteome and acetyl-proteome atlas of three leaf developmental stages. We identified a total of 7,637 proteins and quantified 6,256; of these, 3,232 were classified as differentially accumulated proteins (DAPs). We also identified 3,161 lysine acetylation sites in 1,752 proteins and quantified 2,869 in 1,612 proteins. The acetylation levels at 468 sites were significantly altered across the three developmental stages during periodic albinism; the corresponding proteins were associated with a variety of biological processes. Interestingly, a large number of DAPs and acetylated proteins with increased/decreased acetylation were related to photosynthesis and secondary metabolite biosynthetic pathways, suggesting that the accumulation or acetylation level of these proteins regulates periodic albinism in ‘Anji Baicha.’ Additionally, overlap between succinylome and acetylome among three ‘Anji Baicha’ developmental stages were found. These data provide important insight into the mechanisms of leaf coloration in the tea plant. The mass spectrometry data have been deposited to Proteome X change via the PRIDE partner repository with the data set identifier PXD008134.